Design, synthesis, characterization, and antimicrobial activity of the new 2-{(E)-[(4-aminophenyl)imino]methyl}-4,6-dichlorophenol and its complexes with Co(II), Ni(II), Cu(II) and Zn(II): An experimental and DFT study - Bakirdere, Emine Gulhan; Fellah, Mehmet Ferdi; Canpolat, Erdal; Kaya, Mehmet; Gur, Seher (Serbian Chemical Soc, 2016)
In this study, the complexes of Co(II), Ni(II), Cu(II) and Zn(II) with 2-{(E)-[(4-aminophenyl)imino]methyl}-4,6-dichlorophenol were prepared and characterized by physical, spectral and analytical data. The metal:ligand stoichiometric ratio was 1:2 in all the complexes. The results suggested that the Schiff bases were coordinated to the metal ions through the phenolic oxygens and the azomethine nitrogen to give mononuclear complexes. Their structures were elucidated based on elemental analysis, IR, H-1- and C-13-NMR, UV-Vis, and magnetic susceptibility measurements and thermogravimetric analyses. Both the antibacterial and antifungal activities and the minimum inhibitory concentration (MIC) values of compounds are reported. Among the tested compounds, the most effective compound providing an MIC value of 64 mu g mL(-1) was Zn(L)(2) against Candida tropicalis and Bacillus subtilis. The theoretically optimized geometries of the complexes were tetrahedral structures. The computed stretching frequencies of the C=N, C-O and N-H bonds were in good agreement with the experimental data. All the calculated frequencies fell within about 5 % of the experimental frequency regions.
Keywords: Schiff base; transition metal complex; antibacterial and antifungal activities; DFT